2019
DOI: 10.1016/j.physletb.2019.134924
|View full text |Cite
|
Sign up to set email alerts
|

M2-branes on a constant flux background

Abstract: We describe a compactified Supermembrane, or M2-brane, with 2-form fluxes generated by constant three-forms that are turned on a 2-torus of the target space M 9 × T 2 . We compare this theory with the one describing a 11D M2-brane formulated on M 9 ×T 2 target space subject to an irreducible wrapping condition. We show that the flux generated by the bosonic 3-form under consideration is in a one to one correspondence to the irreducible wrapping condition. After a canonical transformation both Hamiltonians are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(58 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…This follows from the presence of a nontrivial central charge condition [32] that renders the spectrum purely discrete with finite multiplicity [33]. The same results occurs for the M2-brane with nontrivial constant fluxes C ± on the target [26]. This paper is organized as follows.…”
Section: Jhep09(2020)097mentioning
confidence: 89%
See 4 more Smart Citations
“…This follows from the presence of a nontrivial central charge condition [32] that renders the spectrum purely discrete with finite multiplicity [33]. The same results occurs for the M2-brane with nontrivial constant fluxes C ± on the target [26]. This paper is organized as follows.…”
Section: Jhep09(2020)097mentioning
confidence: 89%
“…In this section we review former results found in [26] where it was shown that a M2-brane with C ± fluxes can be interpreted as a M2-brane in a background with central charges. The supersymmetric action of the M2-brane on a generic 11D noncompact background was found by [34].…”
Section: Jhep09(2020)097 2 M2-brane With Constant C ± Fluxesmentioning
confidence: 92%
See 3 more Smart Citations